Altered lipid metabolism in APC-driven colorectal cancer: the potential for therapeutic intervention - Kelson, Courtney O.; Zaytseva, Yekaterina Y. (Frontiers in Oncology, 2024)
Altered lipid metabolism is a well-recognized feature of solid cancers, including colorectal cancer. In colorectal cancer, upregulation of lipid metabolism contributes to initiation, progression, and metastasis; thus, aberrant lipid metabolism contributes to a poor patient outcome. The inactivating mutation of APC, a vital tumor suppressor in the Wnt signaling pathway, is a key event that occurs early in the majority of colorectal cancer cases. The potential crosstalk between lipid metabolism and APC-driven colorectal cancer is poorly understood. This review collectively highlights and summarizes the limited understanding between mutations in APC and the upregulation of Wnt/betacatenin signaling and lipid metabolism. The interconnection between APC inactivation and aberrant lipid metabolism activates Wnt/beta-catenin signaling which causes transcriptome, epigenetic, and microbiome changes to promote colorectal cancer initiation and progression. Furthermore, the downstream effects of this collaborative effort between aberrant Wnt/beta-catenin signaling and lipid metabolism are enhanced stemness, cellular proliferation, prooncogenic signaling, and survival. Understanding the mechanistic link between APC inactivation and alterations in lipid metabolism may foster identification of new therapeutic targets to enable development of more efficacious strategies for prevention and/or treatment of colorectal cancer.